'Imfuno neeMbawelo': ambition, desire and aspiration in South African post-apartheid migration - Sokutu, Litha Buhle Zukile (Social Anthropology, 2017)
Based on fieldwork done in the city centre of Cape Town over two months, coupled with multiple conversations that stem as far back as 2011, this dissertation explores the spirit of ambition and desire, known in Xhosa as 'imfuno'. Articulated as a unit of study, I explore the concept of imfuno and how it manifests itself in the social lives of a group of migrant labourers in Cape Town, particularly in a post-apartheid South Africa loaded with personal expectations, wants and needs. Drawing on theoretical models of covert strategy, politics of suffering and dynamics of social change, this thesis postulates that people's notions of themselves, their aspirations and life-goals are not only interconnected, but also can become driving forces that allow them to withstand and negotiate denigrating socio-economic conditions. Using Cape Town as a site of study, existing as a microcosm for the legacy of apartheid and the history of separation at large in South Africa, the thesis elaborated on notions of space, and how through examining the construction of space, claims of belonging and alterity are created. The way in which my informants were aware of this spatial planning in the city, and were able to strategize around for the purpose of finding meaning and self-actualization, forms a thematic filament in this monograph. Throughout the discussion is the idea of existing in a social system that informants clearly acknowledge as oppressive in light of recent political shifts. Each of the four chapters elaborates of the multi-contextual presence of imfuno, and how it expands and contracts as social actors' expectations mutate as larger macro structures play a role. Like many other post-colonial monographs by anthropologists such as Bank(2011), this dissertation takes a observes and analyses 'classic' works in migration studies and argues for a fluid, constantly changing discourse around the migration and mobility field in anthropology.